NARRATIVE EDITORIAL OF HERITAGE ARCHITECTURE TRANSFORMATION - Harsritanto, Bangun I.R. (MODUL, 2020)
World changed everyday and it’s happened in every life’s aspect without borders. The architecture as part of the culture is one of the life’s aspect that being transformed in every place and periods. Each transformation has narrative reasonings that embedded on the building artefacts. Regardless the functions, the eras, the technologies attached on it, buildings tell us silently their stories. Due to the knowledge seeking and re-implementation, human may learn from the building arounds and telling to the others as their capabilities.